2009
DOI: 10.1088/0268-1242/24/9/095008
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, lattice vibration and mechanical properties of CdTe, ZnTe, MnTe, MgTe, HgTe and their ternary alloys

Abstract: The main representative telluride family, CdTe, ZnTe, MnTe, MgTe and HgTe, and their mixed ternary alloys have been extensively studied, but some points bearing on phonon frequencies properties have never been previously reported or are still not clear. In this paper, we report results on the electronic, lattice dynamical and mechanical properties for this family in the zinc-blende (ZB) structure. Numerical calculations based on the empirical pseudo-potential method under the virtual crystal approximation comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 65 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…They found that the HgTe alloy has an inverted band gap at Г-point with values of −0.8-−0.4 eV using LDA and MBJ-LDA functionals, respectively. Furthermore, Mansri et al [11] studied the electronic, lattice dynamics and mechanical properties for the telluride family (ZnTe, MnTe, HgTe, MgTe and CdTe) and their ternary alloys by the empirical pseudo-potential method within virtual crystal approximation and obtained a good agreement with the available experimental findings. San-Dong and Bang-Gui [12] studied the structural, electronic and optical properties of Hg 1−x Cd x Te (x = 0, 0.25, 0.5, 0.75, 1) within GGA and LDA-mbj functionals.…”
Section: Introductionmentioning
confidence: 71%
“…They found that the HgTe alloy has an inverted band gap at Г-point with values of −0.8-−0.4 eV using LDA and MBJ-LDA functionals, respectively. Furthermore, Mansri et al [11] studied the electronic, lattice dynamics and mechanical properties for the telluride family (ZnTe, MnTe, HgTe, MgTe and CdTe) and their ternary alloys by the empirical pseudo-potential method within virtual crystal approximation and obtained a good agreement with the available experimental findings. San-Dong and Bang-Gui [12] studied the structural, electronic and optical properties of Hg 1−x Cd x Te (x = 0, 0.25, 0.5, 0.75, 1) within GGA and LDA-mbj functionals.…”
Section: Introductionmentioning
confidence: 71%
“…The elements of the elastic stiffness tensor are the principal quantities. [7,11,12] The elements of this tensor are used to calculate the thermal and mechanical quantities of the materials, such as the Debye temperature, elastic stress tensor, elastic strain tensor, Young's modules, Poisson's ratio, bulk modules, shear modulus, isotropy factor, linear compressibility, Cauchy ratio, Born ratio, micro-hardness and sound velocity. [27] We use the following relations to calculate the c 11 , c 12 and c 44 elements: [11]…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The mechanical properties of the II-VI compounds were studied in Refs. [11] and [12]. In the present work, in order to achieve a complete investigate of the feasibility of using the Hg x Mg (1−x) Te ternary compound as a good RT photodetector, we study as a first step the structural and electronic properties of the β -MgTe (shortened name, MgTe) and HMT including the band structure, band gap and effective masses of the electron and hole.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28] Lately, MgTe and its mixed ternary alloys have been extensively studies, containing electronic, lattice dynamical and mechanical properties in zinc-blende structure. 29 However, the Raman and absorption spectra, bonding characters and molecule orbital of MgTe, MgSe, MgS and MgO have not been reported to this day. Moreover, the contrast of their characters has not been achieved.…”
Section: Introductionmentioning
confidence: 99%